From Diagnosis to Recovery: The Life-Changing Benefits of Exercise for Cancer Patients - Koper, Mateusz; Bochenek, Oliwia; Nowak, Aleksandra; Kałuża, Jessica; Konaszczuk, Adrian; Ratyna, Klaudia; Kozyra, Oliwia; Szypuła, Zofia; Paluch, Katarzyna; Skarbek, Małgorzata (Quality in Sport, 2024)
Physical activity has emerged as a crucial component in the comprehensive care of oncological patients, offering significant benefits across the cancer continuum—from prevention to treatment, recovery, and survivorship. This article provides an in-depth exploration of the role of exercise in cancer care, highlighting its potential to improve physical function, reduce treatment-related side effects, enhance mental well-being, and improve overall quality of life. Epidemiological evidence supports the protective effect of regular physical activity in reducing the risk of developing certain cancers, such as breast, colorectal, and endometrial cancer, through mechanisms like hormonal regulation, inflammation reduction, and immune function enhancement. During active cancer treatment, exercise helps combat common side effects such as fatigue, muscle wasting, and cardiovascular decline, while also offering psychological benefits like reduced anxiety and depression. Tailored exercise programs, developed in collaboration with healthcare professionals, are essential for addressing the unique needs of cancer patients, considering factors like cancer type, treatment stage, and comorbidities. Post-treatment, physical activity continues to play a vital role in rehabilitation, reducing the risk of recurrence, and supporting long-term survivorship. Despite the clear benefits, barriers such as physical limitations, psychological distress, and lack of access to resources can hinder patients' ability to engage in regular exercise. Addressing these challenges through personalized care plans, patient education, and supportive interventions is crucial. As research in exercise oncology advances, integrating physical activity into routine cancer care holds promise for improving outcomes and enhancing the overall well-being of cancer patients.